Dramatic and early complete resolution of lobar collapse in young patient of bronchial asthma: a case report from radiologist perspective - Nepal, Pankaj; Kumar, Devendra; Ghimire, Neeta (Journal of Chitwan Medical College, 2018)
To A 30 year old female with known history of bronchial asthma since five years presented to emergency department with acute shortness of breath and left sided pleuritic chest pain since one day. Imaging with initial chest x-ray reveal left lower lobe lung collapse with ipsilateral tracheo-mediastinal shift. On CT scan complete cutoff of the left lower lobe bronchus was seen. With conservative management including inhaled bronchodilators and intravenous corticosteroids and physiotherapy treatment; dramatic and complete resolution of lobar collapse seen within period of 4 days without any residual changes. Such dramatic changes have never been perceived in our radiology experience and literature review, which we report as interesting case.